Faktor Risiko Perioperatif Terhadap Kejadian Delirium Saat Pulih Sadar Setelah Anestesi Umum Pada Pasien Dewasa Yang Menjalani Operasi Elektif Di RSUP Dr Sardjito - Dewi, Wahyu Jati Paramita; Widodo, Untung; Apsari, Ratih Kumala Fajar (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Background. Emergence delirium in anesthesia is a common problem after anesthesia especially in recovery room,but the incidence and risk were unclear. Emergence delirium makes serious complication and impact in morbidity and mortality were no treated properly. So this study built. Objective. To determine the perioperative risk factors of emergence delirium after general anesthesia of elective surgery at Dr Sardjito Hospital. Method. Ninety-nine patients who have surgery under general anesthesia were prospectively observed and variables were potentials perioperative risk factors for delirium at recovery room were dated. The data were statistically analyzed by bivariate and multivariate analysis based on the incidence of delirium after recovery. Results. Total sample of the study were 99 patients who had delirium 55 (55.6%). The results of multivariate analysis showed risk factor of emergence delirium were age 18-25 years old (p=0,045, OR 5,54, 95%CI 1,02-15,189), smoker (p=0,06, OR 6,83, 95%CI 1,769-21,069), alkoholism (p=0,018, OR 10,34, 95%CI 2,09-78,98), ophthalmology (p=0,005, OR 5,43, 95%CI 1,86-32,266), alprazolam premedication (p=0,045, OR 4.035, 95%CI = 1.029-15.819), general anesthesia/ET (p=0,024, OR 5,23, 95%CI 1,697-21,792), duration of surgical procedure > 2 jam (p=0,025, OR 10.320, 95% CI 1.331-79.987), duration 1-2 jam (p=0.023, OR 6.554, 95% CI 1.291-33.266), opioid analgetic (p=0,019, OR 4,15, 95%CI 1,028-17,819) epidural cath (p=0,021, OR 5,83, 95%CI 1,981-20,069), artery line/CVC (p=0,043, OR 9,79, 95% CI 1,08-89,32), DC (p=0.010, OR 0.074. 95%CI 0.010-0.529), blood transfusion and vasopressors (p=0.004, OR 10,38, 95% CI = 2.11-51,08), pain scale/NRS >7 (p=0.049, OR 10.598, 95%CI 0.933-120.386), and NRS 3-7 (p=0.039, OR 5.465, 95%CI 1.091-27.372), PONV dan shivering (p=0.006, OR 3,77, 95% CI = 1.47-9,67). Conclusions. Age 18-25 years old, smoking and alcoholism, ophthalmology surgery, alprazolam premedication, general anesthesia/ET, duration surgery > 1 hour, opioid and epidural catheter analgesia, artery line/CVC, DC, blood transfusion and vasopressor, post operative pain with NRS >3, PONV/shivering have increased risk for emergence delirium.